Antígona González: The never-ending construction of collective memory - Wolfenzon Niego, Carolyn (2022)
Antígona González is a theatrical work or a dramatic poem made up of a collection of texts. The book functions as a collective memory that is constantly created and re-created. The freedom in which the theatrical scenes are altered (in modern dance and theatre) can be interpreted as if they were memories in perpetual construction. The work is written as a pastiche —an accumulation of texts— that include testimonies of a diverse population affected by violence, as well as news stories and online blog posts. Each of these items add their own snippets to this innovative theatrical work that continues to compose itself and recompose itself as if it were a living collage. Antígona González is a unique work because of the way in which it constructs a collective memory through the constant updates and remediations which, in turn, incorporate the voices of those who have been silenced. In turn, it demands the action of the reader or the spectator. Its objective is to empower and embolden the viewer to rise up and make it such that the killings and the disappearances of Mexicans are never forgotten.